1998
DOI: 10.1007/s004170050129
|View full text |Cite
|
Sign up to set email alerts
|

Retroviral vector-mediated gene transfer into keratocytes: in vitro effects of polybrene and protamine sulfate

Abstract: Both polybrene and protamine sulfate can significantly improve the in vitro efficiency of successful retroviral vector-mediated gene transfer into keratocytes. Mild cytotoxic and moderate antiproliferative effects are to be expected in cultured keratocytes with a standard transduction procedure (8 micrograms/ml for 2 h).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 42 publications
1
19
0
Order By: Relevance
“…Several investigators have directly compared the effectiveness of Pb and PS on retroviral vector transduction enhancement and have reported results ranging from similar enhancement (7) to higher efficiencies with PS (23) or higher efficiencies with Pb (6,24). In our studies Pb was more effective than PS, although the difference was less extensive with HI serum.…”
Section: Discussionmentioning
confidence: 51%
“…Several investigators have directly compared the effectiveness of Pb and PS on retroviral vector transduction enhancement and have reported results ranging from similar enhancement (7) to higher efficiencies with PS (23) or higher efficiencies with Pb (6,24). In our studies Pb was more effective than PS, although the difference was less extensive with HI serum.…”
Section: Discussionmentioning
confidence: 51%
“…This adsorption does not depend on the type of receptor and viral envelope and is also temperature-independent. Polybrene is considered non-toxic at low concentrations, but has been found to negatively affect cell proliferation in some cell types, such as keratinocytes, at concentrations greater than 10 µg/mL [16]. In our attempts to transduce hMSCs with lentivirus, we observed that hMSC proliferation was also affected by polybrene.…”
Section: Introductionmentioning
confidence: 79%
“…As polycations improve adenovirusmediated gene transfer, less virus would have to be used, which would improve the therapeutic index by reducing unwanted responses associated with high doses of virus. On the other hand, multiple reports indicate that polycations could exhibit nonspecific cytotoxicity in vivo as well as in vitro (73,74), with some studies demonstrating unacceptable cytotoxicity for DEAE-dextran (74,75) and Polybrene (76,77), at least under some experimental conditions. Therefore, while our study conceptually demonstrates the feasibility of the polycation-mediated improvement of VSV-based OV therapy in vitro, future studies are needed to compare Polybrene and DEAE-dextran to other polycations that could be used safely and effectively in vivo in combination with VSV and ruxolitinib.…”
Section: Figmentioning
confidence: 99%